Recognition and determination of related traits importance with seed yield in chickpea (Cicer aietinum) - Ghorbani, Tayebeh; Cheghamirza, Kianoosh; Bardideh, Kosar; Shoar, Parastoo Basiri (Plant Breeding and Seed Science, 2013)
To study the relationship between seed yield and its components 5 varieties and 18 different genotypes of Cicer arietinum were evaluated. This study was carried out under dryland farming during 2007 in research farm of Razi university. Path analysis showed that in the first level of yield, the highest direct effect was related to biological yield and the highest indirect effect was related to seed number per plant due to biological yield. In second level of yield due to the seed number per plant double seed pod number had the highest direct effect and the highest indirect effect was related to hundreds seed weight due to double the seed pod number. In second level of yield due to biological yield, the highest direct effect was related to high plant and the highest indirect effect was related to high plant due to second branch number. In the third level of yield due to a hundred seed weight, the highest direct effect was related to pod diameter and the highest indirect effect was related to pod length due to pod diameter. Factor analysis showed that 5 factors explained 81.65 percent of the variance. Cluster analysis based on ward method were arranged genotypes in 3 clusters.